Changes in the Muscle Tension of Erector Spinae after the Application of the McKenzie Method in Patients with Chronic Low Back Pain - Hagovska, M.; Takáč, P.; Petrovičová, J. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2014)
Objective: Validation of the effect of the McKenzie method in patients with lumbar spine discopathy. Our aim was to objectively record derangement, according to McKenzie, by monitoring the centralization phenomenon, the sensory and affective dimensions of pain, reduction in the level of disability, and reduction of tension in the erector spinae muscle by means of surface EMG during static activities, in patients with chronic low back pain. The tension of the erector spinae muscle was also measured in healthy individuals in order to compare this to the changes observed in patients with chronic low back pain.Sample: The research sample consisted of 31 patients with MRI diagnosed discopathy. The intervention group (Group 1) was treated with the McKenzie method alongside general physiotherapy. The control group consisted of healthy individuals (n=24) who didn’t receive any therapeutic intervention.Methods: The McGill Pain Questionnaire was used to measure the intensity and type of pain. The Roland Morris Questionnaire (RMQ) was used to measure the degree of disability. The Schuhfried Biofeedback 2000 x-pert 2 channel surface electromyography (EMG) was used to measure the tension of the erector spinae muscle, paravertebrally at the L4 level. The centralization phenomenon was evaluated by means of 4-degree scale.Results: The tension of erector spinae during static activities was found to be significantly lower (p<0.01) in healthy individuals, compared to those in the intervention group prior to treatment. One week after treatment, centralization phenomenon was recorded in 50% of patients, and after 1 month it was recorded in 100% of patients. After 3 months 70% of patients were without pain. One month after the treatment a significant reduction in disability was recorded (p<0.01), and there was a significant reduction in the tension of erector spinae in prone position (p<0.05). Three months after the treatment there was a significant reduction of pain perception (p<0.01), however the significant reduction in disability was not maintained. No significant differences were found in the tone of erector spinae in the intervention group compared to healthy individuals, in prone position. In standing, the erector spinae muscle tension in healthy subjects was consistently significantly higher.Conclusion: An objective reduction of derangement was identified after 1 month and 3 months post treatment. This is based on the centralization phenomenon that occurred, as well as the reduction in the sensory and affective dimensions of pain, degree of disability and tone of erector spinae during static activities. Centralization leads to a continuous reduction in muscle tension. Dysfunction is an intermittent increase of muscle tone, and increases when the muscle is loaded e. g. in standing.
Keywords: low back pain; pain intensity; physiotherapy